Improvement of properties of silver filled epoxy composites via processing method - Mariatti, M. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2012)
Conductive composites consisting of an epoxy matrix and silver flakes were fabricated, and mechanical, thermal and electric properties were investigated as a function of particle concentration and processing techniques. Scanning electron microscope (SEM) was utilized in an attempt to study the effect of the processing method on the distribution of silver flakes in the matrix. As observed by SEM, the use of a homogenizer enhanced the distribution of silver flakes with reducing the particle agglomeration due to the presence of shear force during mixing. The application of shear mixing during the fabrication of conductive polymer composites increased the electric conductivity, flexural modulus, and storage modulus of the silver filled epoxy composite.